(untitled) (Research, Society and Development, 2021)
Mortality due to cardiovascular diseases represents 28% of the total deaths in Brazil in the last five years, being the main cause of death in the world. In order to prevent these events, non-pharmacological and pharmacological measures are used through the use of statins. Simvastatin is in this class, being one of the most prescribed in Brazil due to its wide availability in the health system, although it is well tolerated, not exempt from adverse events and caution regarding its use, requiring monitoring in order to guarantee success in the patient’s pharmacotherapy and well-being. This work aims to outline the profile of use of simvastatin users in Brazil, contributing to the establishment of an increasingly accurate perception in relation to the use of the medication and the problems that can be triggered through its use. A bibliographic review research was carried out based on searches in Scielo and Lilacs databases. The vast majority of the population that uses medications are the elderly, since they are polymedicated due to the presence of more than one comorbidity, thus increasing the risk of problems related to medications, medications in pharmacotherapy and impacts on well-being and patient’s quality of life. The studies found contributed to the characterization of patients who use drugs, observing the absence of specific studies related to the use of simvastatin, making it essential to conduct direct and future research on the profile of use of simvastatin by users.